Toxoplasma gondii infection and associated factors in blood donors from hospital II-2 Tarapoto, Peru, July to December 2019: Infección por Toxoplasma gondii y factores asociados en donantes de sangre de un hospital de la selva peruana - Díaz-Ginéz, Adolfo (2021)
Introduction: Toxoplasmosis is a worldwide parasitic infection caused by Toxoplasma gondii that can be transmitted through blood transfusions. Objectives: To determine the frequency and associated factors of T. gondii infection in blood donors from Hospital II-2 Tarapoto, Peru, July to December 2019. Methods: Analytical cross-sectional study carried out in a sample of 92 donors. Infection was determined by detecting serum IgM and IgG anti T. gondii antibodies by the Elisa technique. Sociodemographic, environmental and habit factors were collected by applying an interview to each volunteer participant. Results: The donor sample was characterized by a median age of 30 years, male gender (76.1%), urban home area (81.5%) and student occupation (34.8%); likewise, 29.4% stated that they ingested non-potable water and 61.9% had contact with earth or sand. 77.2% (95% CI: 68.6 - 85.8) of donors had past infection. No cases of active infection were observed. Contact with cats and domestic animals was associated with infection by T. gondii (p = 0.037; PR = 1.28 and 95% CI = 1.02 - 1.61). Conclusions: Blood donors from Hospital II-2 Tarapoto presented a high frequency of chronic infection by T. gondii. The possible transmission of the parasite through blood transfusion is suggested, for which reason it is recommended to assess the inclusion of toxoplasmosis as a screening test.